2004
DOI: 10.1590/s1519-566x2004000300013
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of Beauveria bassiana with acaricides

Abstract: Compatibilidade de Beauveria bassiana com AcaricidasRESUMO -Visando avaliar a compatibilidade in vitro, entre o fungo entomopatogênico Beauveria bassiana (Bals.) Vuil. e acaricidas, 12 formulações com os ingredientes ativos clorfenapir, fenpiroximate, amitraz, acrinatrim, hexitiazox, abamectina, piridine, dimetoato, piridaphetion, óxido de fenbutatim, azociclotim e cihexatim, foram testadas em três concentrações (concentração Média -CM, metade da CM e duas vezes a CM). Para os parâmetros germinação de conídios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 7 publications
(10 reference statements)
1
24
0
2
Order By: Relevance
“…In the authors opinion germination inhibition decreases the efficiency of pathogena as biocontrol agent, either of those already occurring in the agro-ecosystem or those applied by overflow, associated or not to pesticide products. De Olivera and Neves (2004) evaluated compatibility of B. bassiana with 12 acaricides and showed that Avermectin and the Pyrethroids were more compatible with B. bassiana than the others. This knowledge should facilitate the choice of chemicals with or less harmful to naturally occurring or artificially inoculated beneficial fungi.…”
Section: Introductionmentioning
confidence: 99%
“…In the authors opinion germination inhibition decreases the efficiency of pathogena as biocontrol agent, either of those already occurring in the agro-ecosystem or those applied by overflow, associated or not to pesticide products. De Olivera and Neves (2004) evaluated compatibility of B. bassiana with 12 acaricides and showed that Avermectin and the Pyrethroids were more compatible with B. bassiana than the others. This knowledge should facilitate the choice of chemicals with or less harmful to naturally occurring or artificially inoculated beneficial fungi.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro test techniques that evaluate compatibility of chemicals with entomopathogenic fungi usually make use of different serial dilutions of the chemicals added to a culture medium, making the method both laborious and costly (Oliveira and Neves, 2004;Barci et al, 2009;Asi et al, 2010). This study, however, used the broth dilution method based on (CLSI -M38A).…”
Section: Discussionmentioning
confidence: 99%
“…The objective of the applied methodology was to simulate actual conditions of fungus exposure to the chemical products, as indicated by Oliveira & Neves (2004), and therefore, the responses obtained in the present experiment actually express the interaction between the fungus and the products and their impact on the evaluated parameters.…”
Section: Insecticidesmentioning
confidence: 99%
“…Leger et al, 1991). Germination may also be reduced when certain molecules bind to receptors in the fungal cytoplasm, affecting membrane permeability and enzyme synthesis, changing conidial metabolism (Moore-Landecker1982; Ghini & Kimati 2000;Oliveira & Neves, 2004).…”
Section: Insecticidesmentioning
confidence: 99%